Preparation and evaluation of appertized from snail Helix aspersa M (2015)
This study includes the development and evaluation of snails (Helix aspersa M.) appertized, collected at a heliciculture breeding center, located in Los Niches sector, Curico, Maule region, South-central of Chile. The test was conducted at the Laboratory of Sciences of the Catholic University of Maule, Nuestra Señora del Carmen Campus, Curico. The main objective of this work was to study the influence of appertized on sensory attributes and commercial durability of snail Helix aspersa M. Additionally, some specific objec-tives were proposed as follow: to provide this mollusc with a commercial alternative for it consume, to evaluate itsorganoleptic characteristics and guarantee the product from both the microbiological and nutritional points of view. Three media cover were used (T0: water + NaCl 2%; T1: Water + NaCl 2% + citric acid 0.5% + kilol and T2: extra virgin olive oil + spices + tocopherol). The product was assessed at two different times, after 30 and 90 days of storage. Two sensory evaluations were conducted to measure various organoleptic attributes and acceptability of the appertized by 14 trained panelists. Amino acid, vitamins, cholesterol, acidity, heavy metals, phosphorus and organochlorines analysis were performed. The presence of both total and fecal contaminant microorganisms was determined. Attributes such as color, flavor, aroma, texture and overall acceptability were also measured. Preserves made by T0 and T1 treatments were equally accepted by the panelists. However, preserve from treatment T2 was rejected be-cause of the detection in them of a very dark color, odor and mealy texture. Positive results regarding the content of amino acids, vitamin C and low cholesterol, as well as the absence of pathogenic microorgan-isms were obtained for the three treatments.